2005
DOI: 10.1109/tsp.2005.849196
|View full text |Cite
|
Sign up to set email alerts
|

Widely linear decision-feedback equalizer for time-dispersive linear MIMO channels

Abstract: The paper deals with the transmission over multiple-input/multiple-output channels exhibiting time-dispersion. A minimum mean-square error equalizer based on widely linear processing combined with the decision-feedback (DF) strategy is implemented via finite-impulse-response filters. The proposed equalizer provides considerable performance gain at the expense of a limited increase in computational complexity. The performance analysis has been carried out accounting for mismatch conditions always present in pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Therefore, since for the OPPM-based STBCs here considered, the eigenvalue d 2 min is limited up to two [see the upper bound in (21)], whereas δ 2 max is (obviously) lower bounded by zero see Eq. 22, we conclude that the d 2 min and δ 2 max eigenvalues of the unitary OPPM-based STBCs, attaining the maximum coding gain, must equate…”
Section: Remark 3 On the Achievable Maximum Coding Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, since for the OPPM-based STBCs here considered, the eigenvalue d 2 min is limited up to two [see the upper bound in (21)], whereas δ 2 max is (obviously) lower bounded by zero see Eq. 22, we conclude that the d 2 min and δ 2 max eigenvalues of the unitary OPPM-based STBCs, attaining the maximum coding gain, must equate…”
Section: Remark 3 On the Achievable Maximum Coding Gainmentioning
confidence: 99%
“…Furthermore, in any case, MIMO precoders demand for (very) reliable feedback links to communicate back to the transmitter the path-gains estimates available at the receiver. On the other hand, especially when blind equalization is attempted, MIMO DFEs may be affected by error-propagation phenomena that may (drastically) reduce the coding/diversity gain offered by the employed STBCs see, for example, [21] and references therein for recent contributions on this topic). In principle, the transceiver scheme, proposed in [3] for multipath-impaired SISO systems promises to investigate the above mentioned drawbacks, suffered by MIMO precoders and DFEs.…”
Section: Conclusion and Hints For Future Developmentsmentioning
confidence: 99%
“…For example, an MMSE equalizer and a decision-feedback equalizer (DFE) employing WLP and implemented via finite impulse response (FIR) filters for a MIMO frequency selective channel have been proposed in [21] and [22], respectively. It was concluded that the use of WLP yields considerable performance improvements at the cost of only a limited increase in complexity compared to conventional linear processing.…”
Section: B Modified Isdic Schemementioning
confidence: 99%
“…proposed in [6], [7]. It was concluded that the use of WLP yields considerable performance improvements at the cost of only a limited increase in complexity compared to conventional linear processing.…”
Section: Introductionmentioning
confidence: 99%